2020
DOI: 10.3390/cancers12030565
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Patient-Reported Outcomes following Surgical Treatment of Lymphedema

Abstract: Introduction: Analysis of quality of life (QOL) outcomes is an important aspect of lymphedema treatment since this disease can substantially impact QOL in affected individuals. There are a growing number of studies reporting patient-reported outcomes (PROMs) for patients with lymphedema. The purpose of this study was to conduct a systematic review of outcomes and utilization of PROMs following surgical treatment of lymphedema. Methods: A literature search of four databases was performed up to and including Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 56 publications
5
47
0
Order By: Relevance
“…Significant mean QoL improvements after LVA surgery were reported with consistent results in all follow-up periods until mean follow-up of 32 months. A recent systematic review on QoL following surgical treatment of lymphedema revealed that the majority of previous studies report QoL improvement solely based on the patient's feelings [7]. The reported proportions (range 57-100%) are consistent with the 80% of patients experiencing a positive effect in the current study [7].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Significant mean QoL improvements after LVA surgery were reported with consistent results in all follow-up periods until mean follow-up of 32 months. A recent systematic review on QoL following surgical treatment of lymphedema revealed that the majority of previous studies report QoL improvement solely based on the patient's feelings [7]. The reported proportions (range 57-100%) are consistent with the 80% of patients experiencing a positive effect in the current study [7].…”
Section: Discussionsupporting
confidence: 84%
“…A recent systematic review on QoL following surgical treatment of lymphedema revealed that the majority of previous studies report QoL improvement solely based on the patient's feelings [7]. The reported proportions (range 57-100%) are consistent with the 80% of patients experiencing a positive effect in the current study [7]. The other studies did use validated tools to asses QoL.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Lymphedema has a profound negative impact on patients' quality of life, and PROMs provide insight from patients about their quality of life associated with their condition and how this changes with time and the treatment they have received. [2][3][4] It is therefore essential that the development of PROMs involve patients, and as this systematic review highlights, only Upper Limb Lymphedema (ULL)-27 was developed with patient interviews. Six of the tools involved patient surveys during the development phase, which also may provide validity if the surveys were conducted in an open-question format.…”
mentioning
confidence: 99%
“…Previous systematic reviews have lacked a consensus regarding the most suitable PROM to use. [2][3][4] Although one review found the ULL-27 to have strong psychometric properties, 3 compared with the Lymphedema Life Impact Scale (LLIS) questionnaire, a clinical study of secondary upper extremity lymphedema found the LLIS to be more sensitive for measuring the degree of physical and functional disability. 5 The authors did not conclude which of questionnaires currently available is the From this study, the authors make the case that a current need exists for a valid and reliable lymphedema-specific PROM that adheres to modern development and validation guidelines, including extensive qualitative input from patients.…”
mentioning
confidence: 99%